The Wagner Group as a Tool of Russian Hybrid Warfare - Marek Górka (Polish Political Science Yearbook, 2023)
Unrest, conflicts, and wars in various parts of the world have created huge political and business opportunities for private military companies. They can gather intelligence, provide security for rich and powerful political actors, and provide mercenaries to interest groups worldwide. Private Russian military forces with close ties to President Vladimir Putin are used in war zones and continue expanding their presence in many regions worldwide. The Wagner Group is the most famous Russian mercenary unit. It gained notoriety mainly by supporting Russian forces in the conflict in Ukraine in 2014. At that time, it also provided one of the services that the authorities in the Kremlin particularly appreciate in their actions, and that is the lack of attribution for conducting armed conflicts, thanks to which mercenaries play the role of separatist fighters. Since then, the organisation has been deployed in many countries, including Syria, Libya, Mali, the Central African Republic, Sudan, and Venezuela, always to covertly support representatives of regimes favoured by Putin. Like all other mercenary units in Russia, the Wagner Group does not officially exist, because Russian law does not allow mercenary activities. The article has two main objectives: first, to present an analysis of the activities of the Wagner Group, using the currently available information; second, to prove that the concept of hybrid warfare could best explain the Kremlin’s use of Russian mercenaries.